Optimal enterprise risk management and decision making with shared and dependent risks - Ai, Jing, author; Brockett, Patrick L., author; Wang, Tianyang, author; The Journal of Risk and Insurance, publisher (Colorado State University. Libraries, 2016)
Dynamic enterprise risk management (ERM) entails holistic decision-making for critical corporate functions such as capital budgeting and risk management. The interplay across business divisions, however, is complicated due to their natural interactions through the shared and dependent risk exposures within an intricate corporate structure. This paper develops an integrated optimization framework via a copula-based decision tree interface to facilitate ERM decision making to meet the specified enterprise goal in a multi-period setting. We illustrate our model and provide managerial insights with a case study for a financial services company engaged in both banking and insurance businesses.
Published as: Journal of Risk and Insurance, vol. 84, no. 4, December 2017, pp. 11271169. https://doi.org/10.1111/jori.12140.
Keywords: enterprise risk management (ERM); capital budgeting; risk dependency; copula modeling; decisions under uncertainty